Rubric’s development process for assessment of project management competences - Souza, Mariane (2022)
Assessment rubrics are recognized for their positive effects, being defined as an evaluative instrument that establishes assessment criteria and performance levels. In this sense, assessment rubrics can be associated with professional practices for more authentic assessment processes. In the context of Project Management, the International Project Management Association (IPMA) has developed a framework that establishes the individual competences for professionals working in the area, the Individual Competence Baseline (ICB). The objective of this study is to propose a process of rubric development for competence assessment in Project Management. A rubric for Leadership competence was developed to show the applicability and relevance of the proposed process. The research methodology adopted in the study was Design Science Research. The application and evaluation of this rubric in a pilot study show that the rubric development process allowed the creation of a specific rubric for the assessment of leadership competence. This paper guides those who need to develop and assess project management competences, and it is intended to propose a replicable process for the other ICB competences.